2018
DOI: 10.1080/01443615.2018.1454411
|View full text |Cite
|
Sign up to set email alerts
|

The impact of nuchal cord on umbilical cord blood gas analysis and ischaemia-modified albumin levels in elective C-section

Abstract: This study was designed to evaluate umbilical cord ischaemia-modified albumin (IMA) levels and the cord blood gas parameters of foetuses with or without nuchal cords, at the time of elective C-section. The cross-sectional study population consisted of the patients who were admitted to the Tertiary Care Center between February and June 2015. Women with uncomplicated single term gestations between 37 and 40 completed weeks and scheduled for elective C-sections were included in the study. Fifty cases with a nucha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…They concluded that while there may be changes in the cord pH, it is not clinically significant to change practice patterns. 5 Our study confirmed these findings. Akkaya et al performed a prospective cohort study comparing pregnancies complicated by NC and those without complication and the association with abnormal UA cord pH, Apgar scores, cesarean section rate, or fetal distress on electronic fetal monitoring.…”
Section: Contextsupporting
confidence: 88%
See 1 more Smart Citation
“…They concluded that while there may be changes in the cord pH, it is not clinically significant to change practice patterns. 5 Our study confirmed these findings. Akkaya et al performed a prospective cohort study comparing pregnancies complicated by NC and those without complication and the association with abnormal UA cord pH, Apgar scores, cesarean section rate, or fetal distress on electronic fetal monitoring.…”
Section: Contextsupporting
confidence: 88%
“…Several studies have demonstrated that NC may not be associated with adverse obstetric and perinatal outcomes. 1 2 3 4 5 However, some have noted an increased risk of operative vaginal delivery due to fetal distress and lower Apgar scores. 2 3 4 6 7 Given these mixed data there is little consensus regarding counseling when a NC is identified on ultrasound antenatally or management during labor.…”
mentioning
confidence: 99%